DETERMINANT FACTORS OF THE UTILIZATION OF HEALTH SERVICES FOR JKN-KIS PARTICIPANTS AT THE PUBLIC HEALTH CENTERS IN INDONESIA: A LITERATURE REVIEW - Ningsi, Nadila Puspita; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ational Health Insurance is a state program as part of the National Social Security System, which is implemented using a mandatory social health insurance mechanism. This aims to meet the appropriate basic health needs of the community to be provided to everyone who has paid contributions or whose contributions are paid by the government. This study aimed to determine the determinant factors of the utilization of health services for JKN-KIS participants at the Public Health Centers in Indonesia. The method used in writing this article was a literature review. This study used the Google Scholar search engine, with the article period being 2020-2023. Based on a literature review conducted on relevant articles, the determinant factors for the utilization of health services for JKN-KIS participants at Public Health Centers in Indonesia were JKN participants' perceptions of health services, accessibility factors for health services, attitudes of health workers towards the use of JKN, participants' knowledge of utilization of JKN, and the relationship between disease history and utilization of health services. The government needs to carry out outreach to the public regarding the health service utilization system in national health insurance and evaluate the quality of health services for JKN-KIS participants at Public Health Centers. Keywords: Determinant Factors, JKN-KIS, Health Services, Public Health Center